The problem of diagnosis in psychiatry - from a psychologist’s standpoint - J, Bharath Raj (Journal of All India Institute of Speech and Hearing, 1970)
It is an interesting experience to watch through one of those clinical con- ferences, where important decisions are made regarding the patient. Subsequent to the presentation from the psychiatric and the psychodiagnostic angles, ensues the discussion period, which brings forth a variety of alternative diagnoses, (often incompatible) along with justifications for the same. Many a times the confusion does not facilitate to reach a good diagnosis. All this leaves a mind scientifically trained, with a depressive feeling and a reasonable degree of confusion.